MATHEMATICAL COMMUNICATION ABILITY IN SOLVING SQUARE FUNCTION QUESTIONS VIEWED FROM STUDENTS' LEARNING INTERESTS - Lestari, Yani Septia (Prima: Jurnal Pendidikan Matematika, 2024)
Mathematical communication skills are one of the basic skills that students at the secondary school level must have. This research aims to describe students' mathematical communication skills in solving quadratic function problems based on their learning interests. This research used a descriptive qualitative approach involving 29 class XI B2 students at SMAN Colomadu. Data was collected through questionnaires, tests and interviews and then analyzed using data reduction, presentation and conclusion-drawing techniques. The three subjects represent different levels of learning interest: low, medium, and high. The results show that students with a high interest in learning can fulfil all indicators of mathematical communication. Students with moderate interest can fulfil the second and fourth indicators: Expressing mathematical ideas appropriately using mathematical language and Examining and assessing other people's mathematical thinking and techniques. Students with low interest can only fulfil the fourth indicator: Examining and assessing other people's mathematical thinking and techniques.